2003
DOI: 10.1161/01.str.0000066869.45310.50
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous TAT-GDNF Is Protective After Focal Cerebral Ischemia in Mice

Abstract: Background and Purpose-Delivery of therapeutic proteins into tissues and across the blood-brain barrier is severely limited by their size and biochemical properties. The 11-amino acid human immunodeficiency virus TAT protein transduction domain is able to cross cell membranes and the blood-brain barrier, even when coupled with larger peptides. The present studies were done to evaluate whether TAT-glial line-derived neurotrophic factor (GDNF) fusion protein is protective in focal cerebral ischemia. Methods-Anes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(89 citation statements)
references
References 39 publications
4
85
0
Order By: Relevance
“…Overexpression of CaBD could decrease neuronal death after transient focal ischemia (Yenari et al, 2001). In contrast to the low transfection, PTD can deliver its cargo into brain cells more efficiently across the blood-brain barrier into neurons and astrocytes in the cerebral cortex, striatum, and medulla oblongata (Asoh et al, 2005;Cao et al, 2002;Kilic et al, 2003). After injection of 50 mg/mL PTDCaBD, we detected a number of anti-histidinepositive cells in the subventricular zone, cerebral cortex, and caudate putamen.…”
Section: Discussionmentioning
confidence: 93%
“…Overexpression of CaBD could decrease neuronal death after transient focal ischemia (Yenari et al, 2001). In contrast to the low transfection, PTD can deliver its cargo into brain cells more efficiently across the blood-brain barrier into neurons and astrocytes in the cerebral cortex, striatum, and medulla oblongata (Asoh et al, 2005;Cao et al, 2002;Kilic et al, 2003). After injection of 50 mg/mL PTDCaBD, we detected a number of anti-histidinepositive cells in the subventricular zone, cerebral cortex, and caudate putamen.…”
Section: Discussionmentioning
confidence: 93%
“…Further, PTD-Bcl-xL demonstrated prevention of neuronal death resulting from transient focal ischemia [69]. In another successful in vivo study, Kilic et al [71] demonstrated that intravenous inoculation of PTD-GDNF fusion protein protected neurons from focal cerebral ischemic injury. Similarly, in a non-neurological model, Hotchkiss et al [77] showed that Tat-Bcl-xL fusion protein and PTD-BH4 peptide prevented E.coli-induced human lymphocyte apoptosis ex-vivo and markedly decreased lymphocyte apoptosis in an in-vivo mouse model of sepsis.…”
Section: Potential Of Ptd-fusion Protein Transduction In Vivomentioning
confidence: 98%
“…Subsequently, several other studies have also reported effective biodistribution of therapeutically important proteins in vivo by using PTD [52,[69][70][71][72][73][74][75]. In a previous study, however, no PTD mediated transduction in brain was observed, [46] possibly because beta-gal was chemically conjugated to PTD instead of recombinant fusion protein.…”
Section: Potential Of Ptd-fusion Protein Transduction In Vivomentioning
confidence: 99%
“…As the present study showed that Tat-acp-SRDIYSTDYYR suppressed NGF-induced TRPV1 expression in PC12 cells, Tat-acp-SRDIYSTDYYR likely suppresses the downstream signals of TrkA, which play a crucial role for prolonged inflammatory pain (1, 2, 5). Cell-penetrating peptides including the Tat-derived amino acid sequence administered intravenously are reportedly detected intracellularly in all brain regions (21,22). Therefore in vivo administration of Tat-acp-SRDIYSTDYYR could distribute into peripheral and central neurons and could affect TrkA activity and the downstream signaling.…”
Section: Discussionmentioning
confidence: 99%